SUSCEPTIBILIDAD DE LA PALOMA SILVESTRE (Columba livia) UN VIRUS VELOGÉNICO VISCEROTRÓPICO DE LA ENFERMEDAD DE NEWCASTLE EN CONDICIONES EXPERIMENTALES - Caballero R., Fabiola (2005)
The objective of the study was to asses the susceptibility, pathological effect and serological response of wild pigeons (Columba livia) to Newcastle virus. A total of 28 adult wild pigeons were captured, 14 were inoculated with a velogenic viscerotropic strain of Newcastle virus by oral and nasal route, and the remaining birds were used as a control group. Clinical signs and mortality were recorded. Blood samples were collected for the hemaglutination inhibition technique. Tissue samples from lung and trachea were collected, and cloacal swabs were harvested for virus recovery and histological studies. Birds of the inoculated group showed clinical signs (64%) and mortality (42.8%). The clinical signs (sneezes, ruffled plumage, isolation and lethargy) started at day 4 after inoculation. The 43% of birds showed nervous signs (opisthotonos and tremors of head and neck) and 21% had diarrhea. In the necropsy was observed a widespread congestion and splenomegaly. The microscopic injuries were edema, gliosis, mononuclear perivascular cuffing in brain and cerebellum, loss of cillia, lymphoid infiltration in trachea, lung congestion, proventricular congestion, lymphocitic infiltration in intestines, and lymphoid depletion in spleen. The inoculated group showed the highest antibody titer (4.9) in the second week. The viral recovery was made upon lung and trachea tissues. It was showed that the specie Columba livia was susceptible to the experimental inoculation with a velogenic strain of Newcastle diasease virus.